2019
DOI: 10.1093/abm/kaz049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Community-to-Clinic Navigation Intervention on Colorectal Cancer Screening Among Underserved People

Abstract: Background Colorectal cancer screening remains suboptimal among poor and underserved people. Purpose We tested the effectiveness of a community-to-clinic navigator intervention to guide multicultural, underinsured individuals into primary care clinics to complete colorectal cancer screening. Methods This two-phase behavioral intervention study was conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…30 A recent study has shown that education plus tailored navigation (in person or via phone) addressing individual barriers to screening are the most important components of any educational program aiming to increase adherence to CRC screening. 31 This retrospective study has several limitations. The NCDB is not population-based registry, but rather identifies patients from 1500 commission-accredited cancer programs, and potentially limits the generalizability of our patient population.…”
Section: Discussionmentioning
confidence: 98%
“…30 A recent study has shown that education plus tailored navigation (in person or via phone) addressing individual barriers to screening are the most important components of any educational program aiming to increase adherence to CRC screening. 31 This retrospective study has several limitations. The NCDB is not population-based registry, but rather identifies patients from 1500 commission-accredited cancer programs, and potentially limits the generalizability of our patient population.…”
Section: Discussionmentioning
confidence: 98%
“…The adaptation of the intervention was guided by frameworks established by Card et al [37] albeit with modification. Because we were leveraging an existing intervention, [31][32][33] we did not seek out other materials. Our original intervention was adapted in the five recommended areas: language (words, literacy, cultural references in the message library [TIMS © ] and the training materials); updating research-based information (CRC and screening impact on AIs), images and exemplars for cultural relevance; updating staff training (all navigator training materials); and evaluation materials (REDCap database entry, navigator logs, EHR verifications).…”
Section: Intervention Adaptation Frameworkmentioning
confidence: 99%
“…We developed and tested this tailored navigator intervention (TIMS © ) in a randomized controlled trial design in a mixed African American and older non-Hispanic white population [33]. In a subsequent validating randomized controlled trial using TIMS © , conducted in an urban, underserved, largely Hispanic population, completion of CRC screening was increased almost fourfold in individuals receiving the tailored navigation intervention compared to the control [31].…”
Section: The Tailored Intervention Messaging System © (Tims © )mentioning
confidence: 99%
See 1 more Smart Citation
“…Adopting methods from prior successful tailored messaging research (Lee et al, 2014; Lee-Lin et al, 2015; Menon et al, 2011) and clinic-based promotion of CRC screening (Larkey, Wilson, & Sillanpaa, 2009, 2015; Lee et al, 2014; Lee-Lin et al, 2015; Menon et al, 2011, 2020), a dissemination study was designed and funded by the National Cancer Institute (2012–2017) to demonstrate the use of the tailored messaging approach to navigate individuals from the community to clinics to receive CRC screening. From the time the proposal was conceived and written with community and clinic partners indicating support through letters of commitment to the time of funding and start-up, several communities, demographic, and healthcare policy conditions had changed, presenting challenges to study recruitment and implementation.…”
mentioning
confidence: 99%